METABOLISMO LIPÍDICO DE OÓCITOS DE VACAS DE LEITE SOB ESTRESSE TÉRMICO - Mariane Gabriela Cesar Ribeiro (2022)
The aim of this study was to evaluate the effects of in vivo heat stress in dairy cows on lipid metabolism of cumulus-oocyte complexes (COCs) undergoing IVM. 27 Primiparous Holstein cows were kept in a climate chamber with ad libitum feeding and a constant temperature of 28°C and a temperature-humidity index (THI) of 76 for 7 days (Heat stress - HS) or under constant temperature of 16°C, THI = 60 and receiving the same amount of food as cows submitted to heat stress (Pair-feeding - PF) or ad libitum feeding (Control - C), during the same period. Oocyte cumulus complexes (COCs) were obtained by ovarian slicing technique. Samples were prepared for analysis before (T0) and after (T24) IVM. T0 and T24 COCs were denuded and cumulus cells (CC) and oocytes (Oo) were separately subjected to analyses of lipid content (LiCo) and mitochondrial activity (MA) by fluorescence and confocal microscopy, lipid profile by LC-MS; and gene expression by RT-PCR using the Fluidigm platform. Metaboanalist 5.0 software (heatmap and volcano plot) was used to statistically evaluate the LC-MS results. For fluorescence and gene expression, data were organized in a 2x3 factorial model and analyzed by proc GLM (SAS ondemand). For all analyses, P<0.05 was considered. Among the metabolic pathways evaluated, the greatest number of alterations occurred in CC. The expression of genes that participate in steroid control was affected in HS animals, with reduced DHCR7, and increased CYP11A1. These effects are probably related to the decreased expansion of the CCs observed. HS was the only group that showed a significant increase in LiCo after IVM, in addition to reduced mechanisms that collaborate with the control of lipotoxicity, such as the reduction of ELOVL5, and overall reduction of TG (Oo and CC), mainly those consisting of stearic (18:0), oleic (18:1), and linolenic (18:2) fatty acids (FAs), and reduction of HSPE1 and HSPD1 (CC). Some survival mechanisms were triggered, such as increased expression of MAP2K2 (CC and Oo), FABP3 (CC), SIRT1 (CC and Oo), and MTCH2 (CC and Oo). On the other hand, important pathways for homeothermic control were impaired, HSPA4, HSPA5, HSPA9 (CC and Oo) and ATF4 (CC and Oo) expressions were reduced. Molecular events that participate in chromatin organization also point to reduced HS oocyte competence, such as reduced H2A (CC and Oo) and increased G6PD (CC and Oo) and SETD2 (CC). It is concluded that lipid metabolism is affected by heat stress in dairy cows, affecting steroid production, which impacts cumulus cell expansion. The increase in lipids and mitochondrial activity after IVM, but with impaired lipid profile, with reduction of FAs important for lipotoxicity control. Keywords: oxidative stress, mitochondrial activity, beta-oxidation, lipidom, oocyte maturation